Removing base mist from flue gas emission: article - Ahmad Ramdan, Anis Arina; Zainal, Safari (2018)
Air pollution is a mixture between substances from natural gas with man-made where almost all factories contribute to harmful gases as their waste in the production line. This problem does not only effect human but also to animal and plants. Most studies on treating air pollution are only focus on one compound in the pollution and usually on acid gases compound. However, there are some base compound exists in the atmosphere creating air pollution. In order to overcome this problem, this study has been conducted which aiming to study the removal of various base gas using sulfuric acid solution and to investigate the effect of concentration of sulfuric acid and contact time toward base gas. This research will focused in three types of base, which are ammonia, triethylamine, and diethyl ether. The base gases were passed through various concentration of sulfuric acid with different time contact. Ammonia was removed with 0.05M, 0.1M and 0.5M of sulfuric acid and time taken of 5, 10, 15 and 20 minutes. Triethylamine was removed with 0.01M, 0.05M, 0.1M and 0.5M of sulfuric acid together with time of 10, 15, 20 minutes. Lastly, diethyl ether was removed with time contact of 5, 10, 15 and 20 minutes with 0.01M, 0.05M, 0.1M and 0.5M of sulfuric acid. The data were analyse using Gas Chromatography. Based on the analysis, higher concentration of sulfuric acid with longer contact time shows the most removal of base emission for all type of base. The best concentration and time for removal were the lowest and the shortest. For ammonia, 0.5M of sulfuric acid at 5 minutes achieved 100% efficiency removal. 100% efficiency of removal triethylamine achieved 0.1M for 5 minutes. Lastly, the best condition for diethyl ether is 0.1M of sulfuric for 5 minutes of contact time.